2018
DOI: 10.3390/rs10010118
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radiation Pressure Models for BeiDou-3 I2-S Satellite: Comparison and Augmentation

Abstract: Abstract:As one of the most essential modeling aspects for precise orbit determination, solar radiation pressure (SRP) is the largest non-gravitational force acting on a navigation satellite. This study focuses on SRP modeling of the BeiDou-3 experimental satellite I2-S (PRN C32), for which an obvious modeling deficiency that is related to SRP was formerly identified. The satellite laser ranging (SLR) validation demonstrated that the orbit of BeiDou-3 I2-S determined with empirical 5-parameter Extended CODE (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Zhao et al also presented detailed comparisons between BDS‐2 and BDS‐3e satellites and concluded that a new smoothed yaw attitude mode was adopted by the CAST payload instead of the orbit‐normal mode and that the midnight and noon yaw maneuvers occur when the beta angle (elevation of the Sun above the orbital plane) is approximately between −3° and 3°. Recently, this yaw model for CAST‐manufactured BDS‐3 satellites has been published in Wang et al In addition, the onboard clock of the BDS‐3e satellites also showed improved performance compared with the BDS‐2 clocks. Li et al concluded that there is no obvious inter‐system bias between BDS‐3e and BDS‐2 in the common B1I and B3I signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al also presented detailed comparisons between BDS‐2 and BDS‐3e satellites and concluded that a new smoothed yaw attitude mode was adopted by the CAST payload instead of the orbit‐normal mode and that the midnight and noon yaw maneuvers occur when the beta angle (elevation of the Sun above the orbital plane) is approximately between −3° and 3°. Recently, this yaw model for CAST‐manufactured BDS‐3 satellites has been published in Wang et al In addition, the onboard clock of the BDS‐3e satellites also showed improved performance compared with the BDS‐2 clocks. Li et al concluded that there is no obvious inter‐system bias between BDS‐3e and BDS‐2 in the common B1I and B3I signals.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al concluded that there is no obvious inter‐system bias between BDS‐3e and BDS‐2 in the common B1I and B3I signals. Other dynamic orbit modeling refinements of the solar radiation pressure (SRP) model for BeiDou I2‐S can be found in Wang et al Regarding the aspect of ISL, Yang et al presented timely analysis of the precise orbit determination (POD) results when ISL observations are introduced. The residuals showed a magnitude of 8 cm for the ISL observations and demonstrated an average improvement of 50% when ISLs were included compared with the ground station–only observations (ie, the L‐band measurements).…”
Section: Introductionmentioning
confidence: 99%
“…The modelling approach, as presented in Ziebart et al (2005), was adopted into the operational standards for precise orbit determination of the Jason-1 altimetry satellite (Cerri et al 2010;Zelensky et al 2010). Recently, other research groups have explored a broadly similar approach for modelling SRP on Beidou satellites (Tan et al 2016;Wang et al 2018), on the Gravity Field and Steady-State Ocean Circulation Explorer (GOCE) satellite (Gini 2014) and on QZS-1 (Darugna et al 2018).…”
Section: Introductionmentioning
confidence: 99%